« Ils aiment pas le français » Le rapport au français de futurs enseignants du primaire de la PHBern dans leurs récits de formation et de mobilité. - Robin, Jésabel (Transversales, 2015)
Jésabel Robin has been a lecturer in French for future primary-school teachers at the German-speaking Pädagogische Hochschule Bern (PH IVP) since 2007. She felt that most of her students were reluctant to their professional training in French, yet it is one of the subjects they are training to teach. Her research in language and culture pedagogy adopts social anthropological approaches with a view to study the attitude of the PH IVP students towards French. From mobility mapping to comprehensive interviews in self confrontation, she analyses diverse self-narratives and reveals a wide range of individual and collective representations of and about French. She also focuses on the pivotal effect of institutional experiences such as practical training in teaching French and mobility. These constraints trigger tensions between institutional thinking and individual experiences regarding French but also reveal gaps (so-called « interstices institutionnels ») within the institution itself. The author eventually suggests redesigning a few curricular aspects.